Decreased Glutathione S-transferase Level and Neonatal Hyperbilirubinemia Associated with Glucose-6-phosphate Dehydrogenase Deficiency: A Perspective Review - Al-Abdi, Sameer Yaseen (American Journal of Perinatology, 2017)
Classically, genetically decreased bilirubin conjugation and/or hemolysis account for the mechanisms contributing to neonatal hyperbilirubinemia associated with glucose-6-phosphate dehydrogenase (G6PD) deficiency. However, these mechanisms are not involved in most cases of this hyperbilirubinemia. Additional plausible mechanisms for G6PD deficiency–associated hyperbilirubinemia need to be considered. Glutathione S-transferases (GST) activity depends on a steady quantity of reduced form of glutathione (GSH). If GSH is oxidized, it is reduced back by glutathione reductase, which requires the reduced form of nicotinamide adenine dinucleotide phosphate (NADPH). The main source of NADPH is the pentose phosphate pathway, in which G6PD is the first enzyme. Rat kidney GSH, rat liver GST, and human red blood cell GST levels have been found to positively correlate with G6PD levels in their respective tissues. As G6PD is expressed in hepatocytes, it is expected that GST levels would be significantly decreased in hepatocytes of G6PD-deficient neonates. As hepatic GST binds bilirubin and prevents their reflux into circulation, hypothesis that decreased GST levels in hepatocytes is an additional mechanism contributing to G6PD deficiency–associated hyperbilirubinemia seems plausible. Evidence for and against this hypothesis are discussed in this article hoping to stimulate further research on the role of GST in G6PD deficiency–associated hyperbilirubinemia.
Keywords: glutathione S-transferase; glucose-6-phosphate dehydrogenase deficiency; hyperbilirubinemia; neonate